Experimental evidence on the persistence of output and inflation - Klaus Adam (European Central Bank (ECB), 2005)
This paper presents experimental evidence from a monetary sticky price economy in which output and inflation depend on expected future inflation. With rational inflation expectations, the economy does not generate persistent deviations of output and inflation in response to a monetary shock. In the experimental sessions, however, output and inflation display considerable persistence and regular cyclical patterns. Such behavior emerges because subjects' inflation expectations fail to be captured by rational expectations functions. Instead, a Restricted Perceptions Equilibrium (RPE), which assumes that agents use optimal but 'simple' forecast functions, describes subjects' inflation expectations surprisingly well and explains the observed behavior of output and inflation.
Keywords: E32; E37; C91; 330; Experiments; Output and Inflation Dynamics; Rational Expectations; Restricted Perceptions Equilibrium; Konjunkturtheorie; Inflation; Inflationserwartung; Prognose; Lernprozess; Rationale Erwartung; Test